Who Let the Dog and Cat Out? The Emergence of Stray Animal Care Non-Governmental Organisations in Brunei Darussalam - Alikhan, Nurul Farhanah; Alam, Meredian (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
Until today, the existence of stray animals remains a source of contention between the public and the authorities. Public policy seems to be elusive in regulating this phenomenon, as it presents sociocultural conundrums. While there is a continued unclarity in the government regulations, cultures, and normative values; non-government organisations emerged with autonomous resources to take care of stray animals. The present study examines the efforts of several Non-Governmental Organisations (NGOs) in Brunei that are committed to the rescue and treatment of stray animals via the rising phenomenon of stray animals. Despite receiving no financial support from the Government, these stray animal care organisations consistently forge informal co-operative networks with members of the public and non-governmental organisations; in order to sustain their resources, maintain daily operations, and manage finances and other stray animal-related health issues.